Cayman Islands signs a tax information exchange treaty with the United States (2001)
Reports on the Tax Information Exchange Agreement signed in Washington DC on November 27 2001, which ends the Cayman Islands' status as an offshore tax haven.
Keywords: TAX HAVENS